A taxonomic review of the Afrotropical genus Dragmatucha Meyrick, 1908 (Lepidoptera, Gelechioidea, Lecithoceridae, Torodorinae), with descriptions of eleven new species - Park, Kyu-Tek; Koo, Jun-Mo; Agassiz, David J. L.; Aarvik, Leif (Zootaxa, 2020)
The genus Dragmatucha Meyrick is reviewed and 11 species of a total of 13 are described as new. The new species originate from the Democratic Republic of Congo, Ghana, Kenya, and Uganda. Based on morphological characters, especially the color pattern of both wings, the genus is divided into two species-groups: the proaula species-group with five species (D. proaula Meyrick, 1908; D. galbinea Park, sp. nov.; D. kabarolensis Park, sp. nov.; D. saltualis Park, sp. nov. and D. vittatella Park, sp. nov.) and the hispidula species-group with eight species (D. hispidula Park, 2018; D. goniotes Park, sp. nov.; D. cochliana Park, sp. nov.; D. pedalis Park, sp. nov.; D. ghanaensis Park, sp. nov.; D. crinifrutalis Park, sp. nov.; D. dizostera Park, sp. nov. and D. kakumensis Park, sp. nov.). Adults and male genitalia of all new species are illustrated, but female genitalia are provided only for D. ghanaensis Park, sp. nov. and D. kakumensis Park, sp. nov. When fresh material was available, the analysis of COI sequences was undertaken.